2003
DOI: 10.1016/s1470-0328(02)02929-4
|View full text |Cite
|
Sign up to set email alerts
|

Premature ovarian failure: frequency and risk factors among women attending a network of menopause clinics in Italy

Abstract: Nulliparity and lifelong irregular menstrual cycles are associated with an increased risk of preterm ovarian failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 11 publications
2
2
1
Order By: Relevance
“…12,29-32 In our set of premutation carriers no significant association with menopausal age was seen for these factors.…”
Section: Discussioncontrasting
confidence: 62%
“…12,29-32 In our set of premutation carriers no significant association with menopausal age was seen for these factors.…”
Section: Discussioncontrasting
confidence: 62%
“…There was no association found between age at menarche and POF that was consistent with the results of the Italian study, but controversial results can also be retrieved from literature 11,14,15. As in the present study, insufficient or no cases of ovarian surgery, chemotherapy, or radiotherapy existed to investigate existence of association between these factors and POF.…”
Section: Discussionsupporting
confidence: 88%
“…In the present study, a history of irregular menstruation was found to be strongly associated with POF. This was in line with a large Italian study reporting that the risk of POF and of early menopause was higher among women reporting lifelong irregular menstrual cycles 11. The present study was a case-control study, and the Italian study was cross-sectional study; however, due to lack of clear-cut temporality assessment, in both cases, caution needs to be taken in interpreting the results.…”
Section: Discussionsupporting
confidence: 85%
“…This prevalence of premature menopause among HIV-infected women was higher than the reported prevalence of 1.1–6.3% among women in the general population of HIV-uninfected women enrolled in the American Study of Women's Health Across the Nation cohort, although the sampled populations were different demographically [60, 61]. Other reports have noted comparable mean ages at menopause between HIV-infected and HIV-uninfected women but found a disproportionate number of HIV-infected women with a younger median age for menopause [62, 63].…”
Section: Resultsmentioning
confidence: 83%